Global, regional, and national burden of pulmonary arterial hypertension from 1990 to 2021 and projection to 2050: A systematic analysis for the global burden of disease study 2021 - Changyong Wu; Zhongkai Wang; Yihua Luo; Huang Sun; Ruijie Li; Weijie Liu; Fei Xu; Bingqing Zhang; Yunzhu Peng (PLoS ONE, 2025)
Background Pulmonary arterial hypertension (PAH) is a progressive and incurable syndrome characterized by pulmonary vascular remodeling. Although targeted therapies have advanced, prognosis remains poor, underscoring the need for comprehensive epidemiological evaluations to guide public health strategies and resource allocation. Methods This study assessed the global, regional, and national burden of PAH from 1990 to 2021 using data from the Global Burden of Disease Study (GBD) 2021. Metrics included prevalence, incidence, mortality, and disability-adjusted life years (DALYs), with stratified assessments by geography, gender, age, and socio-demographic index (SDI). Results In 2021, the global PAH burden comprised 191,808 prevalent cases, 43,251 incident cases, 22,021 deaths, and 642,104 DALYs. Age-standardized rates declined consistently over the 32-year period. Population growth was the prominent contributor of the PAH burden, with higher rates in females and older age groups. Prevalence, mortality, and DALYs decreased with higher SDI, whereas incidence showed an inverse trend. The disparity between high and low SDI countries widened, with the slope index of inequality increasing from −5.21 in 1990 to −1.52 in 2021. Predictions revealed that further declines in age-standardized rates of prevalence, mortality, and DALYs from 2022 to 2025, but a rise in incidence. Conclusions A decline in the age-standardized rates of PAH was observed, whereas a persisting high absolute disease burden was evident, clustering among women, older populations, and low-SDI regions.